2022
DOI: 10.1186/s12877-022-03355-2
|View full text |Cite
|
Sign up to set email alerts
|

Life-space, frailty, and health-related quality of life

Abstract: Introduction Life-space and frailty are closely linked to health-related quality of life and understanding their inter-relationship could indicate potential intervention targets for improving quality of life. We set out to examine the relationship between frailty and life-space and their relative impact on quality of life measures. Methods Using cross-sectional data from a population-representative cohort of people aged ≥ 70 years, we assessed qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Interventions are wide-ranging, including nutritional supplementation, medications, and exercise programs, among others ( 2 ). In a study of frailty scores, life-space (a measure of the geographical space in which a person’s life takes place) and quality of life, Chitalu and colleagues found that among people with high frailty scores, those with high life-space had better quality of life than similarly frail people with lower life-space; by contrast, life-space was a less relevant factor to quality of life among non-frail individuals ( 53 ). This finding suggests that specific interventions such as increasing life-space, may preferentially benefit frail individuals compared to their potential benefit on the greater geriatric population overall.…”
Section: Introductionmentioning
confidence: 99%
“…Interventions are wide-ranging, including nutritional supplementation, medications, and exercise programs, among others ( 2 ). In a study of frailty scores, life-space (a measure of the geographical space in which a person’s life takes place) and quality of life, Chitalu and colleagues found that among people with high frailty scores, those with high life-space had better quality of life than similarly frail people with lower life-space; by contrast, life-space was a less relevant factor to quality of life among non-frail individuals ( 53 ). This finding suggests that specific interventions such as increasing life-space, may preferentially benefit frail individuals compared to their potential benefit on the greater geriatric population overall.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, a thorough meta-analysis of 57 research revealed that around 26.8% of the older population suffers from frailty (4). Frailty is not only a major risk factor for mortality in older adults, but is associated with a number of unfavorable events, such as falls (5), fractures (6), hospitalization (7), and reduced quality of life (8). Thus, frailty has become an important public health problem and a global health burden.…”
Section: Introductionmentioning
confidence: 99%